DNAzyme conjugated nanomaterials for biosensing applications - Gong Liang; Lv Yi-Fan; Liang Hao; Huan Shuang-Yan; Zhang Xiao-Bing; Zhang Wei Jun (Reviews in Analytical Chemistry, 2014)
DNAzymes are a series of functional oligonucleotides obtained through in vitro selection and able to catalyze the reaction of substrates with the help of some special cofactors such as metal ions, L-histidine and hemin. Compared with naturally occurring bio-enzymes, DNAzymes are more stable and amenable to modification and preparation. Due to their outstanding properties, DNAzymes have been widely used in biological applications, such as target detection and signal amplification. Nanomaterials, with special characteristics including quantum size effect, high biocompatibility, large surface-to-volume ratio and overall structural robustness, exhibit important application prospects in nanotechnology. By combining with a variety of nanomaterials, DNAzyme achieves a lot of special applications in biochemistry. This review summarizes recent achievements in the field of DNAzyme-conjugated nanomaterials for biosensing applications. For a brief demonstration, nanomaterials including gold nanoparticles, carbon nanomaterials, magnetic nanoparticles and semiconductor quantum dots are taken as examples.